Rational design of block copolymer self-assemblies in photodynamic therapy - Demazeau, Maxime; Gibot, Laure; Mingotaud, Anne-Françoise; Vicendo, Patricia; Roux, Clément; Lonetti, Barbara (Beilstein Journal of Nanotechnology, 2020)
Photodynamic therapy is a technique already used in ophthalmology or oncology. It is based on the local production of reactive oxygen species through an energy transfer from an excited photosensitizer to oxygen present in the biological tissue. This review first presents an update, mainly covering the last five years, regarding the block copolymers used as nanovectors for the delivery of the photosensitizer. In particular, we describe the chemical nature and structure of the block copolymers showing a very large range of existing systems, spanning from natural polymers such as proteins or polysaccharides to synthetic ones such as polyesters or polyacrylates. A second part focuses on important parameters for their design and the improvement of their efficiency. Finally, particular attention has been paid to the question of nanocarrier internalization and interaction with membranes (both biomimetic and cellular), and the importance of intracellular targeting has been addressed.
Keywords: intracellular targeting; micelles; photodynamic therapy (PDT); photochemistry; polymer; self-assembly

(untitled) - Schwartz, R. S. (N. Engl. J. Med., 2004)

(untitled) - Matsumura, Y.; Maeda, H. (Cancer Res., 1986)

(untitled) - Maeda, H. (Bioconjugate Chem., 2010)

(untitled) - Bertrand, N.; Leroux, J.-C. (J. Controlled Release, 2012)

(untitled) - Fang, J.; Nakamura, H.; Maeda, H. (Adv. Drug Delivery Rev., 2011)

(untitled) - Knop, K.; Hoogenboom, R.; Fischer, D.; Schubert, U. S. (Angew. Chem., Int. Ed., 2010)

(untitled) - Matyjaszewski, K.; Spanswick, J. (Mater. Today, 2005)

(untitled) - Riehemann, K.; Schneider, S. W.; Luger, T. A.; Godin, B.; Ferrari, M.; Fuchs, H. (Angew. Chem., Int. Ed., 2009)

(untitled) - Dionzou, M.; Morère, A.; Roux, C.; Lonetti, B.; Marty, J.-D.; Mingotaud, C.; Joseph, P.; Goudounèche, D.; Payré, B.; Léonetti, M.; Mingotaud, A.-F. (Soft Matter, 2016)

(untitled) - Crucho, C. I. C. (ChemMedChem, 2015)

(untitled) - Eetezadi, S.; Ekdawi, S. N.; Allen, C. (Adv. Drug Delivery Rev., 2015)

(untitled) - Bobo, D.; Robinson, K. J.; Islam, J.; Thurecht, K. J.; Corrie, S. R. (Pharm. Res., 2016)

(untitled) - Weissig, V.; Pettinger, T. K.; Murdock, N. (Int. J. Nanomed., 2014)

(untitled) - Weissig, V.; Guzman-Villanueva, D. (Int. J. Nanomed., 2015)

(untitled) - Obaid, G.; Broekgaarden, M.; Bulin, A.-L.; Huang, H.-C.; Kuriakose, J.; Liu, J.; Hasan, T. (Nanoscale, 2016)

(untitled) - Bashkatov, A. N.; Genina, E. A.; Kochubey, V. I.; Tuchin, V. V. (J. Phys. D: Appl. Phys., 2005)

(untitled) - Dougherty, T. J.; Grindey, G. B.; Fiel, R.; Weishaupt, K. R.; Boyle, D. G. (J. Natl. Cancer Inst., 1975)

(untitled) - Lucky, S. S.; Soo, K. C.; Zhang, Y. (Chem. Rev., 2015)

(untitled) - Li, T.; Yan, L. (Pharmaceuticals, 2018)

(untitled) - Master, A.; Livingston, M.; Sen Gupta, A. (J. Controlled Release, 2013)

(untitled) - Ben Mihoub, A.; Larue, L.; Moussaron, A.; Youssef, Z.; Colombeau, L.; Baros, F.; Frochot, C.; Vanderesse, R.; Acherar, S. (Molecules, 2018)

(untitled) - Debele, T. A.; Peng, S.; Tsai, H.-C. (Int. J. Mol. Sci., 2015)

(untitled) - Sun, W.; Zhao, X.; Fan, J.; Du, J.; Peng, X. (Small, 2019)

(untitled) - Protti, S.; Albini, A.; Viswanathan, R.; Greer, A. (Photochem. Photobiol., 2017)

(untitled) - Lamch, Ł.; Pucek, A.; Kulbacka, J.; Chudy, M.; Jastrzębska, E.; Tokarska, K.; Bułka, M.; Brzózka, Z.; Wilk, K. A. (Adv. Colloid Interface Sci., 2018)

(untitled) - Shi, X.; Zhang, H.; Jin, W.; Liu, W.; Yin, H.; Li, Y.; Dong, H. (J. Photochem. Photobiol., B, 2019)

(untitled) - Mordon, S.; Cochrane, C.; Tylcz, J. B.; Betrouni, N.; Mortier, L.; Koncar, V. (Photodiagn. Photodyn. Ther., 2015)

(untitled) - Mohammad-Hadi, L.; MacRobert, A. J.; Loizidou, M.; Yaghini, E. (Nanoscale, 2018)

(untitled) - Gibot, L.; Lemelle, A.; Till, U.; Moukarzel, B.; Mingotaud, A.-F.; Pimienta, V.; Saint-Aguet, P.; Rols, M.-P.; Gaucher, M.; Violleau, F.; Chassenieux, C.; Vicendo, P. (Biomacromolecules, 2014)

(untitled) - Berwin Singh, S. V.; Kim, J.; Park, H.; Khang, G.; Lee, D. (Macromol. Res., 2017)

(untitled) - Chu, M.; Li, H.; Wu, Q.; Wo, F.; Shi, D. (Biomaterials, 2014)

(untitled) - Gjuroski, I.; Furrer, J.; Vermathen, M. (ChemPhysChem, 2018)

(untitled) - Montanha, M. C.; Silva, L. L.; Pangoni, F. B. B.; Cesar, G. B.; Gonçalves, R. S.; Caetano, W.; Hioka, N.; Tominaga, T. T.; Consolaro, M. E. L.; Diniz, A.; Kimura, E. (J. Photochem. Photobiol., B, 2017)

(untitled) - Vilsinski, B. H.; Gerola, A. P.; Enumo, J. A.; Campanholi, K. da S. S.; Pereira, P. C. de S.; Braga, G.; Hioka, N.; Kimura, E.; Tessaro, A. L.; Caetano, W. (Photochem. Photobiol., 2015)

(untitled) - Zhiyentayev, T. M.; Boltaev, U. T.; Solov'eva, A. B.; Aksenova, N. A.; Glagolev, N. N.; Chernjak, A. V.; Melik-Nubarov, N. S. (Photochem. Photobiol., 2014)

(untitled) - Han, Y.; Chen, Z.; Zhao, H.; Zha, Z.; Ke, W.; Wang, Y.; Ge, Z. (J. Controlled Release, 2018)

(untitled) - Jing, C.; Wang, R.; Ou, H.; Li, A.; An, Y.; Guo, S.; Shi, L. (Chem. Commun., 2018)

(untitled) - Lamch, Ł.; Tylus, W.; Jewgiński, M.; Latajka, R.; Wilk, K. A. (J. Phys. Chem. B, 2016)

(untitled) - Li, J.; Yao, S.; Wang, K.; Lu, Z.; Su, X.; Li, L.; Yuan, C.; Feng, J.; Yan, S.; Kong, B.; Song, K. (Cancer Sci., 2018)

(untitled) - Wennink, J. W. H.; Liu, Y.; Mäkinen, P. I.; Setaro, F.; de la Escosura, A.; Bourajjaj, M.; Lappalainen, J. P.; Holappa, L. P.; van den Dikkenberg, J. B.; al Fartousi, M.; Trohopoulos, P. N.; Ylä-Herttuala, S.; et al. (Eur. J. Pharm. Sci., 2017)

(untitled) - Yang, T.; Liu, L.; Deng, Y.; Guo, Z.; Zhang, G.; Ge, Z.; Ke, H.; Chen, H. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Grossen, P.; Witzigmann, D.; Sieber, S.; Huwyler, J. (J. Controlled Release, 2017)

(untitled) - Yu, W.; Ye, M.; Zhu, J.; Wang, Y.; Liang, C.; Tang, J.; Tao, H.; Shen, Y. (Nanomedicine (N. Y., NY, U. S.), 2018)

Advanced Polymers in Medicine - Calles, J. A.; Bermúdez, J.; Vallés, E.; Allemandi, D.; Palma, S. (Polymers in Ophthalmology, 2015)

(untitled) - Pound-Lana, G. E. N.; Garcia, G. M.; Trindade, I. C.; Capelari-Oliveira, P.; Pontifice, T. G.; Vilela, J. M. C.; Andrade, M. S.; Nottelet, B.; Postacchini, B. B.; Mosqueira, V. C. F. (Mater. Sci. Eng., C, 2019)

(untitled) - Huang, Y.; Ma, D.; Pan, S.; Lin, P.; Lin, Y.; Yang, H.; Peng, Y. (J. Nanopart. Res., 2015)

(untitled) - Jang, W.-D.; Nishiyama, N.; Zhang, G.-D.; Harada, A.; Jiang, D.-L.; Kawauchi, S.; Morimoto, Y.; Kikuchi, M.; Koyama, H.; Aida, T.; Kataoka, K. (Angew. Chem., Int. Ed., 2005)

(untitled) - Chen, H.; Xiao, L.; Anraku, Y.; Mi, P.; Liu, X.; Cabral, H.; Inoue, A.; Nomoto, T.; Kishimura, A.; Nishiyama, N.; Kataoka, K. (J. Am. Chem. Soc., 2014)

(untitled) - Zhang, G.-D.; Harada, A.; Nishiyama, N.; Jiang, D.-L.; Koyama, H.; Aida, T.; Kataoka, K. (J. Controlled Release, 2003)

(untitled) - Zhao, L.; Ma, R.; Li, J.; Li, Y.; An, Y.; Shi, L. (Biomacromolecules, 2008)

(untitled) - Zheng, R.; Wu, Z.; Yan, Y.; Wang, J.; Huang, J. (RSC Adv., 2015)

(untitled) - Castriciano, M. A.; Zagami, R.; Casaletto, M. P.; Martel, B.; Trapani, M.; Romeo, A.; Villari, V.; Sciortino, M. T.; Grasso, L.; Guglielmino, S.; Scolaro, L. M.; Mazzaglia, A. (Biomacromolecules, 2017)

(untitled) - Conte, C.; Scala, A.; Siracusano, G.; Sortino, G.; Pennisi, R.; Piperno, A.; Miro, A.; Ungaro, F.; Sciortino, M. T.; Quaglia, F.; Mazzaglia, A. (Colloids Surf., B, 2016)

(untitled) - Xiong, H.; Zhou, D.; Zheng, X.; Qi, Y.; Wang, Y.; Jing, X.; Huang, Y. (Chem. Commun., 2017)

(untitled) - Fleige, E.; Quadir, M. A.; Haag, R. (Adv. Drug Delivery Rev., 2012)

(untitled) - Saravanakumar, G.; Kim, J.; Kim, W. J. (Adv. Sci., 2017)

(untitled) - Py-Daniel, K. R.; Namban, J. S.; de Andrade, L. R.; de Souza, P. E. N.; Paterno, L. G.; Azevedo, R. B.; Soler, M. A. G. (Eur. J. Pharm. Biopharm., 2016)

(untitled) - Vilsinski, B. H.; Witt, M. A.; Barbosa, P. M.; Montanha, M. C.; Nunes, C. S.; Bellettini, I. C.; de Castro, L. V.; Sato, F.; Baesso, M. L.; Muniz, E. C.; Caetano, W. (J. Mol. Liq., 2018)

(untitled) - Synatschke, C. V.; Nomoto, T.; Cabral, H.; Förtsch, M.; Toh, K.; Matsumoto, Y.; Miyazaki, K.; Hanisch, A.; Schacher, F. H.; Kishimura, A.; Nishiyama, N.; Müller, A. H. E.; et al. (ACS Nano, 2014)

(untitled) - Wang, Q.; Li, J.-M.; Yu, H.; Deng, K.; Zhou, W.; Wang, C.-X.; Zhang, Y.; Li, K.-H.; Zhuo, R.-X.; Huang, S.-W. (Biomater. Sci., 2018)

(untitled) - Wang, S.; Yuan, F.; Chen, K.; Chen, G.; Tu, K.; Wang, H.; Wang, L.-Q. (Biomacromolecules, 2015)

(untitled) - Ren, H.; Liu, J.; Su, F.; Ge, S.; Yuan, A.; Dai, W.; Wu, J.; Hu, Y. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Yuan, P.; Ruan, Z.; Jiang, W.; Liu, L.; Dou, J.; Li, T.; Yan, L. (J. Mater. Chem. B, 2018)

(untitled) - Hu, H.; Yan, X.; Wang, H.; Tanaka, J.; Wang, M.; You, W.; Li, Z. (J. Mater. Chem. B, 2019)

(untitled) - Liu, L.; Ruan, Z.; Yuan, P.; Li, T.; Yan, L. (Nanotheranostics, 2018)

(untitled) - Till, U.; Gibot, L.; Vicendo, P.; Rols, M.-P.; Gaucher, M.; Violleau, F.; Mingotaud, A.-F. (RSC Adv., 2016)

(untitled) - Till, U.; Gibot, L.; Mingotaud, C.; Vicendo, P.; Rols, M.-P.; Gaucher, M.; Violleau, F.; Mingotaud, A.-F. (Nanotechnology, 2016)

(untitled) - Shen, L.; Huang, Y.; Chen, D.; Qiu, F.; Ma, C.; Jin, X.; Zhu, X.; Zhou, G.; Zhang, Z. (Theranostics, 2017)

(untitled) - Prasad, P.; Gordijo, C. R.; Abbasi, A. Z.; Maeda, A.; Ip, A.; Rauth, A. M.; DaCosta, R. S.; Wu, X. Y. (ACS Nano, 2014)

(untitled) - Sun, J.; Birnbaum, W.; Anderski, J.; Picker, M.-T.; Mulac, D.; Langer, K.; Kuckling, D. (Biomacromolecules, 2018)

(untitled) - Anderski, J.; Mahlert, L.; Sun, J.; Birnbaum, W.; Mulac, D.; Schreiber, S.; Herrmann, F.; Kuckling, D.; Langer, K. (Int. J. Pharm., 2019)

(untitled) - Pasparakis, G.; Manouras, T.; Vamvakaki, M.; Argitis, P. (Nat. Commun., 2014)

(untitled) - Li, Y.; Lv, S.; Song, Z.; Dang, J.; Li, X.; He, H.; Xu, X.; Zhou, Z.; Yin, L. (Nanoscale, 2018)

(untitled) - Li, J.; Wei, K.; Zuo, S.; Xu, Y.; Zha, Z.; Ke, W.; Chen, H.; Ge, Z. (Adv. Funct. Mater., 2017)

(untitled) - Li, J.; Meng, X.; Deng, J.; Lu, D.; Zhang, X.; Chen, Y.; Zhu, J.; Fan, A.; Ding, D.; Kong, D.; Wang, Z.; Zhao, Y. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Li, X.; Gao, M.; Xin, K.; Zhang, L.; Ding, D.; Kong, D.; Wang, Z.; Shi, Y.; Kiessling, F.; Lammers, T.; Cheng, J.; Zhao, Y. (J. Controlled Release, 2017)

(untitled) - Liu, F.; Ma, Y.; Xu, L.; Liu, L.; Zhang, W. (Biomater. Sci., 2015)

(untitled) - Sheng, Z.; Hu, D.; Zheng, M.; Zhao, P.; Liu, H.; Gao, D.; Gong, P.; Gao, G.; Zhang, P.; Ma, Y.; Cai, L. (ACS Nano, 2014)

(untitled) - Tian, J.; Xu, L.; Xue, Y.; Jiang, X.; Zhang, W. (Biomacromolecules, 2017)

(untitled) - Wang, T.; Wang, D.; Yu, H.; Wang, M.; Liu, J.; Feng, B.; Zhou, F.; Yin, Q.; Zhang, Z.; Huang, Y.; Li, Y. (ACS Nano, 2016)

(untitled) - Lovell, J. F.; Liu, T. W. B.; Chen, J.; Zheng, G. (Chem. Rev., 2010)

(untitled) - Ibrahimova, V.; Denisov, S. A.; Vanvarenberg, K.; Verwilst, P.; Préat, V.; Guigner, J.-M.; McClenaghan, N. D.; Lecommandoux, S.; Fustin, C.-A. (Nanoscale, 2017)

(untitled) - Choi, Y.; Weissleder, R.; Tung, C.-H. (ChemMedChem, 2006)

(untitled) - Campo, M. A.; Gabriel, D.; Kucera, P.; Gurny, R.; Lange, N. (Photochem. Photobiol., 2007)

(untitled) - Lee, S. J.; Park, K.; Oh, Y.-K.; Kwon, S.-H.; Her, S.; Kim, I.-S.; Choi, K.; Lee, S. J.; Kim, H.; Lee, S. G. (Biomaterials, 2009)

(untitled) - Li, L.; Bae, B.-c.; Tran, T. H.; Yoon, K. H.; Na, K.; Huh, K. M. (Carbohydr. Polym., 2011)

(untitled) - Li, Y.; Lin, T.-y.; Luo, Y.; Liu, Q.; Xiao, W.; Guo, W.; Lac, D.; Zhang, H.; Feng, C.; Wachsmann-Hogiu, S.; Walton, J. H.; Cherry, S. R.; et al. (Nat. Commun., 2014)

(untitled) - Xue, Y.; Tian, J.; Xu, L.; Liu, Z.; Shen, Y.; Zhang, W. (Eur. Polym. J., 2019)

(untitled) - Kim, W. L.; Cho, H.; Li, L.; Kang, H. C.; Huh, K. M. (Biomacromolecules, 2014)

(untitled) - Gao, D.; Lo, P.-C. (J. Controlled Release, 2018)

(untitled) - Wang, W.; Lin, L.; Ma, X.; Wang, B.; Liu, S.; Yan, X.; Li, S.; Tian, H.; Yu, X. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Fang, J.; Šubr, V.; Islam, W.; Hackbarth, S.; Islam, R.; Etrych, T.; Ulbrich, K.; Maeda, H. (Eur. J. Pharm. Biopharm., 2018)

(untitled) - Wang, Y.; Wei, G.; Zhang, X.; Xu, F.; Xiong, X.; Zhou, S. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Xu, L.; Liu, L.; Liu, F.; Cai, H.; Zhang, W. (Polym. Chem., 2015)

(untitled) - Huang, Y.; Qiu, F.; Shen, L.; Chen, D.; Su, Y.; Yang, C.; Li, B.; Yan, D.; Zhu, X. (ACS Nano, 2016)

(untitled) - Yuan, Y.; Xu, S.; Zhang, C.-J.; Liu, B. (Polym. Chem., 2016)

(untitled) - Wallat, J. D.; Wek, K. S.; Chariou, P. L.; Carpenter, B. L.; Ghiladi, R. A.; Steinmetz, N. F.; Pokorski, J. K. (Polym. Chem., 2017)

(untitled) - Zhang, Y.; Wang, C.-X.; Huang, S.-W. (Nanomaterials, 2018)

(untitled) - Cheng, L.; Kamkaew, A.; Sun, H.; Jiang, D.; Valdovinos, H. F.; Gong, H.; England, C. G.; Goel, S.; Barnhart, T. E.; Cai, W. (ACS Nano, 2016)

(untitled) - Zheng, Y.; Lu, H.; Jiang, Z.; Guan, Y.; Zou, J.; Wang, X.; Cheng, R.; Gao, H. (J. Mater. Chem. B, 2017)

(untitled) - Liu, X.; Yang, G.; Zhang, L.; Liu, Z.; Cheng, Z.; Zhu, X. (Nanoscale, 2016)

(untitled) - Obata, M.; Tanaka, S.; Mizukoshi, H.; Ishihara, E.; Takahashi, M.; Hirohara, S. (J. Polym. Sci., Part A: Polym. Chem., 2017)

(untitled) - Li, L.; Cho, H.; Kim, S.; Kang, H. C.; Huh, K. M. (Carbohydr. Polym., 2015)

(untitled) - Que, Y.; Liu, Y.; Tan, W.; Feng, C.; Shi, P.; Li, Y.; Xiaoyu, H. (ACS Macro Lett., 2016)

(untitled) - Wang, H.; Chao, Y.; Liu, J.; Zhu, W.; Wang, G.; Xu, L.; Liu, Z. (Biomaterials, 2018)

(untitled) - Yuan, Z.; Yu, S.; Cao, F.; Mao, Z.; Gao, C.; Ling, J. (Polym. Chem., 2018)

(untitled) - Zhang, Y.; He, L.; Wu, J.; Wang, K.; Wang, J.; Dai, W.; Yuan, A.; Wu, J.; Hu, Y. (Biomaterials, 2016)

(untitled) - Pelaz, B.; del Pino, P.; Maffre, P.; Hartmann, R.; Gallego, M.; Rivera-Fernandez, S.; de la Fuente, J. M.; Nienhaus, G. U.; Parak, W. J. (ACS Nano, 2015)

(untitled) - D’souza, A. A.; Shegokar, R. (Expert Opin. Drug Delivery, 2016)

(untitled) - Wolfram, J.; Yang, Y.; Shen, J.; Moten, A.; Chen, C.; Shen, H.; Ferrari, M.; Zhao, Y. (Colloids Surf., B, 2014)

(untitled) - Wang, X.; Wang, J.; Li, J.; Huang, H.; Sun, X.; Lv, Y. (J. Drug Delivery Sci. Technol., 2018)

(untitled) - Hu, D.; Zhong, L.; Wang, M.; Li, H.; Qu, Y.; Liu, Q.; Han, R.; Yuan, L.; Shi, K.; Peng, J.; Qian, Z. (Adv. Funct. Mater., 2019)

(untitled) - Khatri, V.; Bhatia, S.; Achazi, K.; Deep, S.; Kohli, E.; Sharma, S. K.; Haag, R.; Prasad, A. K. (RSC Adv., 2017)

(untitled) - Liu, L.; Ruan, Z.; Li, T.; Yuan, P.; Yan, L. (Biomater. Sci., 2016)

(untitled) - Zhang, C.; Wang, Y.; Zhao, Y.; Liu, H.; Zhao, Y.; Li, X.; Lin, Q. (Nanomaterials, 2019)

(untitled) - Sudimack, J.; Lee, R. J. (Adv. Drug Delivery Rev., 2000)

(untitled) - Walters, C. L.; Arend, R. C.; Armstrong, D. K.; Naumann, R. W.; Alvarez, R. D. (Gynecol. Oncol., 2013)

(untitled) - Leone, J. P.; Bhargava, R.; Theisen, B. K.; Hamilton, R. L.; Lee, A. V.; Brufsky, A. M. (Oncotarget, 2015)

(untitled) - Torchilin, V. P.; Lukyanov, A. N.; Gao, Z.; Papahadjopoulos-Sternberg, B. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Roby, A.; Erdogan, S.; Torchilin, V. P. (Eur. J. Pharm. Biopharm., 2006)

(untitled) - Chang, M.-H.; Pai, C.-L.; Chen, Y.-C.; Yu, H.-P.; Hsu, C.-Y.; Lai, P.-S. (Nanomaterials, 2018)

(untitled) - Henderson, B. W.; Dougherty, T. J. (Photochem. Photobiol., 1992)

(untitled) - Dang, J.; He, H.; Chen, D.; Yin, L. (Biomater. Sci., 2017)

(untitled) - Sen Gupta, A. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2017)

(untitled) - Cheng, Y.; Cheng, H.; Jiang, C.; Qiu, X.; Wang, K.; Huan, W.; Yuan, A.; Wu, J.; Hu, Y. (Nat. Commun., 2015)

(untitled) - Liu, Y.; Meng, X.; Bu, W. (Coord. Chem. Rev., 2019)

(untitled) - Li, X.; Zheng, B.-D.; Peng, X.-H.; Li, S.-Z.; Ying, J.-W.; Zhao, Y.; Huang, J.-D.; Yoon, J. (Coord. Chem. Rev., 2019)

(untitled) - Luby, B. M.; Walsh, C. D.; Zheng, G. (Angew. Chem., Int. Ed., 2019)

(untitled) - Shum, J.; Leung, P. K.-K.; Lo, K. K.-W. (Inorg. Chem., 2019)

(untitled) - Pucelik, B.; Gürol, I.; Ahsen, V.; Dumoulin, F.; Dąbrowski, J. M. (Eur. J. Med. Chem., 2016)

(untitled) - Tan, X.; Luo, S.; Long, L.; Wang, Y.; Wang, D.; Fang, S.; Ouyang, Q.; Su, Y.; Cheng, T.; Shi, C. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Glavas, L.; Olsén, P.; Odelius, K.; Albertsson, A.-C. (Biomacromolecules, 2013)

(untitled) - Glavas, L.; Odelius, K.; Albertsson, A.-C. (Polym. Adv. Technol., 2015)

(untitled) - Kakde, D.; Taresco, V.; Bansal, K. K.; Magennis, E. P.; Howdle, S. M.; Mantovani, G.; Irvine, D. J.; Alexander, C. (J. Mater. Chem. B, 2016)

(untitled) - Zhang, L.; Eisenberg, A. (Polym. Adv. Technol., 1998)

(untitled) - Bacinello, D.; Garanger, E.; Taton, D.; Tam, K. C.; Lecommandoux, S. (Biomacromolecules, 2014)

(untitled) - Geng, Y.; Dalhaimer, P.; Cai, S.; Tsai, R.; Tewari, M.; Minko, T.; Discher, D. E. (Nat. Nanotechnol., 2007)

(untitled) - Cai, S.; Vijayan, K.; Cheng, D.; Lima, E. M.; Discher, D. E. (Pharm. Res., 2007)

(untitled) - Geng, Y.; Discher, D. E. (Polymer, 2006)

(untitled) - Yue, T.; Xu, Y.; Sun, M.; Zhang, X.; Huang, F. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Vácha, R.; Martinez-Veracoechea, F. J.; Frenkel, D. (Nano Lett., 2011)

(untitled) - Williford, J.-M.; Santos, J. L.; Shyam, R.; Mao, H.-Q. (Biomater. Sci., 2015)

(untitled) - Yokoyama, M.; Sugiyama, T.; Okano, T.; Sakurai, Y.; Naito, M.; Kataoka, K. (Pharm. Res., 1993)

(untitled) - Miller, T.; Rachel, R.; Besheer, A.; Uezguen, S.; Weigandt, M.; Goepferich, A. (Pharm. Res., 2012)

(untitled) - Wieczorek, S.; Krause, E.; Hackbarth, S.; Röder, B.; Hirsch, A. K. H.; Börner, H. G. (J. Am. Chem. Soc., 2013)

(untitled) - Hamaguchi, T.; Matsumura, Y.; Suzuki, M.; Shimizu, K.; Goda, R.; Nakamura, I.; Nakatomi, I.; Yokoyama, M.; Kataoka, K.; Kakizoe, T. (Br. J. Cancer, 2005)

(untitled) - Zuo, C.; Peng, J.; Cong, Y.; Dai, X.; Zhang, X.; Zhao, S.; Zhang, X.; Ma, L.; Wang, B.; Wei, H. (J. Colloid Interface Sci., 2018)

(untitled) - Ping, J.-t.; Peng, H.-s.; Duan, W.-b.; You, F.-t.; Song, M.; Wang, Y.-q. (J. Mater. Chem. B, 2016)

(untitled) - Rao, J.; Khan, A. (J. Am. Chem. Soc., 2013)

(untitled) - Niedre, M.; Patterson, M. S.; Wilson, B. C. (Photochem. Photobiol., 2002)

(untitled) - Moan, J.; Berg, K. (Photochem. Photobiol., 1991)

(untitled) - Knop, K.; Mingotaud, A.-F.; El-Akra, N.; Violleau, F.; Souchard, J.-P. (Photochem. Photobiol. Sci., 2009)

(untitled) - Ferreira, M.; Chaves, L. L.; Lima, S. A. C.; Reis, S. (Int. J. Pharm., 2015)

(untitled) - Feng, C.; Yuan, X.; Chu, K.; Zhang, H.; Ji, W.; Rui, M. (Int. J. Biol. Macromol., 2019)

(untitled) - Liu, Y.; Wang, Y.; Zhao, J. (Int. J. Biol. Macromol., 2019)

(untitled) - Izadiyan, Z.; Basri, M.; Fard Masoumi, H. R.; Abedi Karjiban, R.; Salim, N.; Kalantari, K. (Mater. Sci. Eng., C, 2019)

(untitled) - Eskandari, Z.; Kazdal, F.; Bahadori, F.; Ebrahimi, N. (J. Drug Delivery Sci. Technol., 2018)

(untitled) - Shi, C.; Sun, Y.; Wu, H.; Zhu, C.; Wei, G.; Li, J.; Chan, T.; Ouyang, D.; Mao, S. (Int. J. Pharm., 2016)

(untitled) - Zhao, F.; Zhao, Y.; Liu, Y.; Chang, X.; Chen, C.; Zhao, Y. (Small, 2011)

(untitled) - Cheng, L.-C.; Jiang, X.; Wang, J.; Chen, C.; Liu, R.-S. (Nanoscale, 2013)

(untitled) - Sandez-Macho, I.; Casas, M.; Lage, E. V.; Rial-Hermida, M. I.; Concheiro, A.; Alvarez-Lorenzo, C. (Colloids Surf., B, 2015)

(untitled) - Yaroslavov, A. A.; Sitnikova, T. A.; Rakhnyanskaya, A. A.; Yaroslavova, E. G.; Sybachin, A. V.; Melik-Nubarov, N. S.; Khomutov, G. B. (Colloid Polym. Sci., 2017)

(untitled) - Schwieger, C.; Blaffert, J.; Li, Z.; Kressler, J.; Blume, A. (Langmuir, 2016)

(untitled) - Ramadurai, S.; Kohut, A.; Sarangi, N. K.; Zholobko, O.; Baulin, V. A.; Voronov, A.; Keyes, T. E. (J. Colloid Interface Sci., 2019)

(untitled) - Wilkosz, N.; Jamróz, D.; Kopeć, W.; Nakai, K.; Yusa, S.-i.; Wytrwal-Sarna, M.; Bednar, J.; Nowakowska, M.; Kepczynski, M. (J. Phys. Chem. B, 2017)

(untitled) - Palominos, M. A.; Vilches, D.; Bossel, E.; Soto-Arriaza, M. A. (Colloids Surf., B, 2016)

(untitled) - Zhang, W.; Haman, K. J.; Metzger, J. M.; Hackel, B. J.; Bates, F. S.; Lodge, T. P. (Langmuir, 2017)

(untitled) - Montis, C.; Till, U.; Vicendo, P.; Roux, C.; Mingotaud, A. F.; Violleau, F.; Demazeau, M.; Berti, D.; Lonetti, B. (Nanoscale, 2018)

(untitled) - Zaki, A. M.; Carbone, P. (Langmuir, 2017)

(untitled) - Houang, E. M.; Haman, K. J.; Kim, M.; Zhang, W.; Lowe, D. A.; Sham, Y. Y.; Lodge, T. P.; Hackel, B. J.; Bates, F. S.; Metzger, J. M. (Mol. Pharmaceutics, 2017)

(untitled) - Raman, A. S.; Pajak, J.; Chiew, Y. C. (Chem. Phys. Lett., 2018)

(untitled) - Guan, Z.; Wang, L.; Lin, J. (Biomacromolecules, 2017)

(untitled) - Wang, T.; Bai, J.; Jiang, X.; Nienhaus, G. U. (ACS Nano, 2012)

(untitled) - Chen, H.; Kim, S.; Li, L.; Wang, S.; Park, K.; Cheng, J.-X. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Kerdous, R.; Sureau, F.; Bour, A.; Bonneau, S. (Int. J. Pharm., 2015)

(untitled) - Till, U.; Gibot, L.; Mingotaud, A.-F.; Ehrhart, J.; Wasungu, L.; Mingotaud, C.; Souchard, J.-P.; Poinso, A.; Rols, M.-P.; Violleau, F.; Vicendo, P. (Molecules, 2016)

(untitled) - Wan, J.; Sun, L.; Wu, P.; Wang, F.; Guo, J.; Cheng, J.; Wang, C. (Polym. Chem., 2018)

(untitled) - Bugaj, A. M. (Photochem. Photobiol. Sci., 2011)

(untitled) - Castano, A. P.; Demidova, T. N.; Hamblin, M. R. (Photodiagn. Photodyn. Ther., 2004)

Ciba Foundation Symposium 146 - Photosensitizing Compounds: Their Chemistry, Biology and Clinical Use - Moan, J.; Berg, K.; Kvam, E.; Western, A.; Malik, Z.; Rück, A.; Schneckenburger, H. (Intracellular Localization of Photosensitizers, 1989)

(untitled) - Ehrenberg, B.; Montana, V.; Wei, M. D.; Wuskell, J. P.; Loew, L. M. (Biophys. J., 1988)

(untitled) - Oseroff, A. R.; Ohuoha, D.; Ara, G.; McAuliffe, D.; Foley, J.; Cincotta, L. (Proc. Natl. Acad. Sci. U. S. A., 1986)

(untitled) - Castro, D. J.; Saxton, R. E.; Fetterman, H. R.; Castro, D. J.; Ward, P. H. (Otolaryngol.–Head Neck Surg., 1988)

(untitled) - Yu, Z.; Pan, W.; Li, N.; Tang, B. (Chem. Sci., 2016)

(untitled) - Han, K.; Zhang, W.-Y.; Zhang, J.; Lei, Q.; Wang, S.-B.; Liu, J.-W.; Zhang, X.-Z.; Han, H.-Y. (Adv. Funct. Mater., 2016)

(untitled) - Huang, H.; Yu, B.; Zhang, P.; Huang, J.; Chen, Y.; Gasser, G.; Ji, L.; Chao, H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Liu, L.-H.; Qiu, W.-X.; Zhang, Y.-H.; Li, B.; Zhang, C.; Gao, F.; Zhang, L.; Zhang, X.-Z. (Adv. Funct. Mater., 2017)

(untitled) - Berg, K.; Selbo, P. K.; Prasmickaite, L.; Tjelle, T. E.; Sandvig, K.; Moan, J.; Gaudernack, G.; Fodstad, Ø.; Kjølsrud, S.; Anholt, H. (Cancer Res., 1999)

(untitled) - Weyergang, A.; Berstad, M. E. B.; Bull-Hansen, B.; Olsen, C. E.; Selbo, P. K.; Berg, K. (Photochem. Photobiol. Sci., 2015)

(untitled) - Ohtsuki, T.; Miki, S.; Kobayashi, S.; Haraguchi, T.; Nakata, E.; Hirakawa, K.; Sumita, K.; Watanabe, K.; Okazaki, S. (Sci. Rep., 2015)

(untitled) - Bøe, S. L.; Hovig, E. (Ther. Delivery, 2013)

(untitled) - Jin, H.; Lovell, J. F.; Chen, J.; Ng, K.; Cao, W.; Ding, L.; Zhang, Z.; Zheng, G. (Photochem. Photobiol. Sci., 2011)

(untitled) - Liu, C.; Chen, Z.; Wang, Z.; Li, W.; Ju, E.; Yan, Z.; Liu, Z.; Ren, J.; Qu, X. (Nanoscale, 2016)

(untitled) - Lee, C.-S.; Na, K. (Biomacromolecules, 2014)

(untitled) - Liu, G.; Hu, J.; Zhang, G.; Liu, S. (Bioconjugate Chem., 2015)

(untitled) - Shieh, M.-J.; Hsu, C.-Y.; Huang, L.-Y.; Chen, H.-Y.; Huang, F.-H.; Lai, P.-S. (J. Controlled Release, 2011)

(untitled) - Li, S.-Y.; Qiu, W.-X.; Cheng, H.; Gao, F.; Cao, F.-Y.; Zhang, X.-Z. (Adv. Funct. Mater., 2017)

(untitled) - Ahn, W. S.; Bae, S. M.; Huh, S. W.; Lee, J. M.; Namkoong, S. E.; Han, S.-J.; Kim, C. K.; Kim, J.-K.; Kim, Y.-W. (Int. J. Gynecol. Cancer, 2004)

(untitled) - Kim, J.; Santos, O. A.; Park, J.-H. (J. Controlled Release, 2014)

(untitled) - Jia, H.-R.; Jiang, Y.-W.; Zhu, Y.-X.; Li, Y.-H.; Wang, H.-Y.; Han, X.; Yu, Z.-W.; Gu, N.; Liu, P.; Chen, Z.; Wu, F.-G. (J. Controlled Release, 2017)

(untitled) - Fulda, S.; Galluzzi, L.; Kroemer, G. (Nat. Rev. Drug Discovery, 2010)

(untitled) - Semenza, G. L. (Science, 2007)

(untitled) - Battogtokh, G.; Ko, Y. T. (Nanomedicine (N. Y., NY, U. S.), 2017)

(untitled) - Marrache, S.; Dhar, S. (Proc. Natl. Acad. Sci. U. S. A., 2012)

Manipulating Mitochondrial Function - Marrache, S.; Pathak, R. K.; Dhar, S. (Mitochondrial Medicine, 2015)

(untitled) - Sonawane, N. D.; Szoka, F. C.; Verkman, A. S. (J. Biol. Chem., 2003)

(untitled) - Sharma, A.; Soliman, G. M.; Al-Hajaj, N.; Sharma, R.; Maysinger, D.; Kakkar, A. (Biomacromolecules, 2012)

(untitled) - Yang, G.; Xu, L.; Xu, J.; Zhang, R.; Song, G.; Chao, Y.; Feng, L.; Han, F.; Dong, Z.; Li, B.; Liu, Z. (Nano Lett., 2018)

(untitled) - Wei, Y.; Zhou, F.; Zhang, D.; Chen, Q.; Xing, D. (Nanoscale, 2016)

(untitled) - Zhou, F.; Xing, D.; Wu, B.; Wu, S.; Ou, Z.; Chen, W. R. (Nano Lett., 2010)

(untitled) - Lv, W.; Zhang, Z.; Zhang, K. Y.; Yang, H.; Liu, S.; Xu, A.; Guo, S.; Zhao, Q.; Huang, W. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hinde, E.; Thammasiraphop, K.; Duong, H. T. T.; Yeow, J.; Karagoz, B.; Boyer, C.; Gooding, J. J.; Gaus, K. (Nat. Nanotechnol., 2017)

(untitled) - El-Akra, N.; Noirot, A.; Faye, J.-C.; Souchard, J.-P. (Photochem. Photobiol. Sci., 2006)

(untitled) - Tian, X.; Zhu, Y.; Zhang, M.; Luo, L.; Wu, J.; Zhou, H.; Guan, L.; Battaglia, G.; Tian, Y. (Chem. Commun., 2017)

(untitled) - Schwarz, D. S.; Blower, M. D. (Cell. Mol. Life Sci., 2016)

(untitled) - Lin, S.; Zhang, L.; Lei, K.; Zhang, A.; Liu, P.; Liu, J. (Cell Stress Chaperones, 2014)

(untitled) - Wang, M.; Kaufman, R. J. (Nat. Rev. Cancer, 2014)

(untitled) - Cubillos-Ruiz, J. R.; Bettigole, S. E.; Glimcher, L. H. (Cell, 2017)

(untitled) - Dai, L.; Cai, R.; Li, M.; Luo, Z.; Yu, Y.; Chen, W.; Shen, X.; Pei, Y.; Zhao, X.; Cai, K. (Chem. Mater., 2017)

(untitled) - Zhao, L.; Kim, T.-H.; Kim, H.-W.; Kim, S. Y. (Int. J. Polym. Mater. Polym. Biomater., 2015)

(untitled) - Seah, G. L.; Yu, J. H.; Yang, M. Y.; Kim, W. J.; Kim, J.-H.; Park, K.; Cho, J.-W.; Kim, J. S.; Nam, Y. S. (J. Controlled Release, 2018)

(untitled) - Seah, G. L.; Yu, J. H.; Koo, B. I.; Lee, D. J.; Nam, Y. S. (J. Mater. Chem. B, 2018)

(untitled) - Faria, M.; Björnmalm, M.; Thurecht, K. J.; Kent, S. J.; Parton, R. G.; Kavallaris, M.; Johnston, A. P. R.; Gooding, J. J.; Corrie, S. R.; Boyd, B. J.; Thordarson, P.; Whittaker, A. K.; et al. (Nat. Nanotechnol., 2018)